'A Giant with Clay Feet': Quebec Students and their Historical Consciousness of the Nation. Issue 2 (1st May 2013) - Lévesque, Stéphane; Létourneau, Jocelyn; Gani, Raphaël
Abstract : The aim of this paper is to explore French Canadian (Québec) students' historical consciousness of the nation through the lens of Social Identity Theory (SIT). Relying on a sample of 142 Quebéc's historical narratives written by Francophone Québécois students, the paper revisits findings from a previous study on the historical consciousness of young Québécois. Informed by SIT principles, our narrative analysis shows how most Franco-Québécois categorize the past in homogenous categories (e.g., the imperialist Anglophone; the surviving Francophone) and frame their stories into particular modes of present-day orientations. Implications of this studyfor history education are also discussed.